Performance Assessment of a Porous Radiant Cook Stove Fueled with Blend of Waste Vegetable Oil (WVO) and Kerosene. (February 2019) - Kaushik, Lav Kumar; Muthukumar, P
Abstract: In India, around 58% of the total population which is more than 780 million people, still rely on solid fuels for cooking [1]. Exploring various sources of energy supply for cooking applications and technological progress towards the efficient design of cookstoves are of current importance. In this paper, the performances of Waste Vegetable Oil (WVO) operated Porous Kerosene Pressure Cookstove (PKPs) and Conventional Kerosene Pressure Cookstove (CKPs) are presented. The effect of input power (1.5-3 kW) on thermal efficiency and emission characteristics are also examined and compared for both the stoves. The measured thermal efficiency is found in the range of 37.8-45.3% for PKPs, while for CKPs, it is in the range of 28.6-36.2%. Emissions measurements show high values of CO and NOX in the range of 905-1300 ppm and 84-180 ppm, respectively, for CKPs. Whereas, because of proper combustion in PKPs, the same are found in the range of 361-664 ppm, and 13.8-47 ppm. Results from Controlled Cooking Test (CCT) showed that by using PKPs one can save about 49 min of cooking time and 59.2% fuel consumption, on a daily basis. From Techno-economic Assessment (TEA), annual saving and cumulative present worth of annual savings over the life of the PKPs are found as Rs. 2, 055 /- and Rs. 16, 817 /-, respectively. The cumulative present worth of annual savings is comparatively larger than the capital cost of the PKPs (Rs. 780 /-). Similarly, calculated Internal Rate of Return (IRR) and payback period are estimated as 268.5% and less than 5 months, respectively. Calculated IRR is much higher than the rate of return (8%) and compared with the life of the cook-stove (10 years) the payback period is very small.